2021
DOI: 10.1007/s00029-021-00664-z
|View full text |Cite
|
Sign up to set email alerts
|

Higher rank Clifford indices of curves on a K3 surface

Abstract: Let (X, H) be a polarized K3 surface with $$\mathrm {Pic}(X) = \mathbb {Z}H$$ Pic ( X ) = Z H , and let $$C\in |H|$$ C ∈ | H | be a smooth curve of genus g. We give a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Most of this can be found in [Bri08]. A review of it can be found in [FL21]. Let (𝑆, 𝐻) be a polarized K3 surface with a Picard group generated by H. We use the same heart of bounded t-structure Coh 𝛽,𝐻 (𝑆) as above and define the central charge as…”
Section: Bridgeland Stability On K3 Surfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of this can be found in [Bri08]. A review of it can be found in [FL21]. Let (𝑆, 𝐻) be a polarized K3 surface with a Picard group generated by H. We use the same heart of bounded t-structure Coh 𝛽,𝐻 (𝑆) as above and define the central charge as…”
Section: Bridgeland Stability On K3 Surfacesmentioning
confidence: 99%
“…Let Γ(𝑥) = 𝐻 2 2 𝑥 2 − 𝛾(𝑥) and Γ + to be the region above Γ. Then Bridgeland showed that (𝛼, 𝛽) with 𝛼 > Γ(𝛽) defines a stability condition 𝜎 𝛼,𝛽 = (Coh 𝛽,𝐻 (𝑋), 𝑍 𝛼,𝛽 ) on K3 surfaces [Bri08,FL21] by using Theorem 2.9. The slope is defined to be − (𝑍 𝛼,𝛽 ) (𝑍 𝛼,𝛽 ) .…”
Section: Bridgeland Stability On K3 Surfacesmentioning
confidence: 99%
“…Riemann-Roch directly implies a stronger Bogomolov-Gieseker inequality on S 2,2 , and shifting the logic of Section 3.2 back to forward gear implies the desired Clifford bounds. These Clifford bound arguments yield new results even for planar curves [29].…”
Section: 3mentioning
confidence: 77%
“…Among others, one of the important consequences of the BG inequality is the existence of Bridgeland stability conditions on surfaces [AB13,Bri07,Bri08]. The theory of Bridgeland stability conditions on surfaces has been applied to various classical problems in algebraic geometry such as birational geometry [ABCH13, BMW14, CH14, CH15, CH16, CHW17, LZ16, LZ18], Brill-Noether problem [Bay18,BL17], higher rank Clifford indices [FL18,Li19,Kos20a], and so on.…”
Section: Introductionmentioning
confidence: 99%